Developing new varieties of deep-rooted crops: silicon and agroecosystem services - Zimin Li; Yunqiang Wang; Zhaoliang Song (npj Sustainable Agriculture)
Developing new varieties of deep-rooted crops may enhance silicon uptake and agroecosystem services. This enhancement is involved in three vital ecosystem processes: (i) increasing crop silicon uptake in deep horizons where it is more readily available as Si(OH4), (ii) contributing to storing more stable organic carbon at depth via root decomposition and deep pedogenic pathways, and (iii) accelerating CO2 transformation into stored or leached alkalinity via deep silicate weathering.